Additive Prognostic Value of Echocardiographic Global Longitudinal and Global Circumferential Strain to Electrocardiographic Criteria in Patients With Heart Failure Undergoing Cardiac Resynchronization Therapy. (June 2016) - Delgado-Montero, Antonia; Tayal, Bhupendar; Goda, Akiko; Ryo, Keiko; Marek, Josef J.; Sugahara, Masataka; Qi, Zhi; Althouse, Andrew D.; Saba, Samir; Schwartzman, David; Gorcsan, John
Abstract : Background—: Response to cardiac resynchronization therapy is most favorable in patients with heart failure with QRS duration ≥150 ms and left bundle branch block and less predictable in those with QRS width 120 to 149 ms or non–left bundle branch block. Methods and Results—: We studied 205 patients with heart failure referred for cardiac resynchronization therapy with QRS ≥120 ms and ejection fraction ⩽35%. We tested the hypothesis that contractile function using speckle-tracking echocardiographic global circumferential strain (GCS) from 2 short-axis views and global longitudinal strain (GLS) from 3 apical views add prognostic value to electrocardiographic criteria. There were 112 patients (55%) with GLS >−9% and 136 patients (66%) with GCS >−9%. During 4 years, 81 patients reached the combined primary end point (death, circulatory support, or transplant) and 120 reached the secondary end point (heart failure hospitalization or death). Both GLS >−9% and GCS >−9% were associated with increased risk of unfavorable events as follows: for the primary end point (hazard ratio=2.91; 95% confidence interval, 1.88–4.49; P <0.001) and (hazard ratio=3.73; 95% confidence interval, 2.39–5.82; P <0.001) for the secondary end point (hazard ratio=2.10; 95% confidence interval, 1.45–3.05; P <0.001) and (hazard ratio=3.25; 95% confidence interval, 2.23–4.75; P <0.001). In a prespecified subgroup of 120 patients with QRS 120 to 149 ms or non–left bundle branch block, significant associations of baseline GLS and GCS and outcomes remained: P =0.014 and P =0.002 for the primary end point and P =0.049 and P =0.001 for the secondary end point. Global strain measures had additive prognostic value to routine clinical or electrocardiographic parameters ( P <0.001). Conclusions—: Baseline GCS and GLS were significantly associated with long-term outcome after cardiac resynchronization therapy and had additive prognostic value to routine clinical and electrocardiographic selection criteria for cardiac resynchronization therapy. Abstract : Supplemental Digital Content is available in the text.